2005
DOI: 10.1108/17415650580000034
|View full text |Cite
|
Sign up to set email alerts
|

Personal Investigator: A therapeutic 3D game for adolecscent psychotherapy

Abstract: Although mental health problems increase markedly during adolescent years, therapists often find it difficult to engage with adolescents. The majority of disturbed adolescents do not receive professional mental health care and of those who do fewer still will fully engage with the therapeutic process (Offer et al. 1991; US Surgeon General 1999). Personal Investigator (PI) is a 3D computer game specifically designed to help adolescents overcome mental health problems such as depression and help them engage more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 18 publications
1
69
0
2
Order By: Relevance
“…For example, one study on using a computer game in a therapeutic session, reported that clients found it easier to talk while looking at the screen. (Coyle et al, 2005). It also found that the introduction of the game had an empowering effect on the adolescent clients.…”
Section: Supporting Mental Health Interventionsmentioning
confidence: 86%
“…For example, one study on using a computer game in a therapeutic session, reported that clients found it easier to talk while looking at the screen. (Coyle et al, 2005). It also found that the introduction of the game had an empowering effect on the adolescent clients.…”
Section: Supporting Mental Health Interventionsmentioning
confidence: 86%
“…• Videogames as a Therapeutic Setting:Videogamesallowparticipantstoexperiencenovelty andchallengewhenengaginginfictionalactivitieswithoutreallifeconsequences (Washburn& Gulledge,1995).Playingvideogameshasalsobeenusedtoestablishaneffectivepatient-therapist relationship,particularlywithyoungpeople (Ceranoglu,2010b).Furthermore,psychotherapyhas beenconductedexclusivelyinvideogamesettings (Coyle,Matthews,Sharry,Nisbet,&Doherty, 2005).Forinstance,throughgameimmersion,anxiouspatientscanbepresentedwithaversive stimuliviaavideogametoprogressivelyeliminatetheiranxiety.Adoptingfictionalroleshas alsobeenusedforencouragingthepracticeofhealthybehaviorsanddevelopingsocialskills (Brownetal.,1997;Lieberman,2001). …”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are described in Coyle et al (2005). This paper describes the results of a larger scale evaluation in which PI was made available to therapists in 10 clinics.…”
Section: P R O O F O N L Ymentioning
confidence: 99%
“…A detailed description of the decisions made in developing PI -for example why was SFT chosen -is beyond the scope of this paper (for more detailed description see Coyle, 2007;Coyle et al, 2005). It is, however, important to state that PI is primarily a characterbased game.…”
Section: Personal Investigatormentioning
confidence: 99%
See 1 more Smart Citation